Contrasting heterozygosity-fitness correlations across life in a long-lived seabird - Bichet, Coraline; Sauer-Gürth, Hedwig; Wink, Michael (Molecular ecology, 2019)
Selection is a central force underlying evolutionary change and can vary in strength and direction, for example across time and space. The fitness consequences of individual genetic diversity have often been investigated by testing for multilocus heterozygosity-fitness correlations (HFCs), but few studies have been able to assess HFCs across life stages and in both sexes. Here, we test for HFCs using a 26-year longitudinal individual-based data set from a large population of a long-lived seabird (the common tern, Sterna hirundo), where 7,974 chicks and breeders of known age were genotyped at 15 microsatellite loci and sampled for life-history traits over the complete life cycle. Heterozygosity was not correlated with fledging or post-fledging prospecting probabilities, but was positively correlated with recruitment probability. For breeders, annual survival was not correlated with heterozygosity, but annual fledgling production was negatively correlated with heterozygosity in males and highest in intermediately heterozygous females. The contrasting HFCs among life stages and sexes indicate differential selective processes and emphasize the importance of assessing fitness consequences of traits over complete life histories.
First published: 20 December 2018
Gesehen am 13.09.2019